Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1039/b819283a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical competitive hybridization assay for DNA detection using osmium tetroxide-labelled signalling strands

Abstract: In this report, we present sequence-specific DNA detection by means of a competitive hybridization assay with osmium tetroxide-labelled signalling strands. The labelling of the signalling strands has been performed using protective strands to preserve the recognition site of these single strands for hybridization with the immobilized capture probes. At optimized measuring conditions and especially assay temperature, we could detect the presence of 25 nM target DNA within 30 minutes, whereas the non-complementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Compared to label-based electrochemical DNA detection studies, our simple work does not contain long experimental steps [35,36] expensive electrodes and oligonucleotides labelled with À SH group [31,35,36,42,55].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to label-based electrochemical DNA detection studies, our simple work does not contain long experimental steps [35,36] expensive electrodes and oligonucleotides labelled with À SH group [31,35,36,42,55].…”
Section: Resultsmentioning
confidence: 99%
“…Panke et al [31] reported a competitive binding protocol and used methylene blue as electroactive label for the determination of DNA single base mismatches in combination with differential pulse voltammetry. Duwensee et al [42] presented sequence-specific DNA detection by means of a competitive hybridization assay with osmium tetroxide-labeled signaling probes and they could detected 25 nM of target DNA in 30 minutes time.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature DNA sensors are reported with considerably lower detection limits [30, 37 -39], however the sensor described here does not use any amplification step and thus compares to other systems using direct redox label detection [40].…”
Section: Quantificationmentioning
confidence: 99%
“…Secondly, a reporter strand can be utilized that binds onto the target in addition and right beside to the capture probe [61]. Thirdly, in a competitive assay, a labeled signaling strand can be used that will be displaced by the target and therefore will lead to signal decrease ("switch off") upon hybridization with the target [62,80].…”
Section: Use Of Covalent Markersmentioning
confidence: 99%